Racial disparities in receipt of standard chemoradiation in anal squamous cell carcinoma, an analysis of the National Cancer Database. (11th December 2020) - Bian, Shelly X.; Chen, Dennis H.; Lin, Eugene
Abstract: Background: Standard treatment for locally advanced anal squamous cell carcinoma (SCC) consists of concurrent chemoradiation. We evaluated whether racial differences exist in the receipt of standard treatment and its association with survival. Methods: From the National Cancer Database, we identified patients diagnosed with anal SCC (Stages 2–3) between 2004 and 2015. Using logistic regression, we evaluated racial differences in the probability of receiving standard chemoradiation. We used Cox proportional hazards models to evaluate associations between race, receipt of standard therapy and survival. Results: Our analysis included 19, 835 patients. Patients receiving standard chemoradiation had better survival than patients receiving nonstandard therapy (hazard ratio [HR] 0.64; 95% confidence interval [CI] 0.61–0.68; p  < 0.001). Compared to White patients, Black patients were less likely to receive standard therapy (odds ratio [OR] 0.85; 95% CI 0.76–0.96; p  < 0.008). We observed no statistical difference in mortality between Black and White patients overall (HR 1.05, 95% CI 0.97–1.15; p  = 0.24). However, for the subgroup of patients receiving nonstandard therapy, Black patients had an increased mortality risk compared to White patients (HR 1.17, CI 1.01–1.35; p  = 0.034). We observed no survival differences in the subgroup of patients receiving standard treatment (HR 1.00, CI 0.90–1.11, p  = 0.99). Conclusion: Standard treatment in anal SCC is associated with better survival, but Black patients are less likely to receive standard treatment than White patients. Although Black patients had higher mortality than White patients in the subgroup of patients receiving nonstandard therapy, this difference was ameliorated in the subset receiving standard therapy. Abstract : Black patients are less likely than White patients to receive standard chemoradiation, which is associated with improved survival. While no racial differences in survival were observed overall, there was significantly lower survival in Black versus White patients who did not receive standard therapy.